List-strength effects in older adults in recognition and free recall. - Sahakyan, Lili (Memory & Cognition, 2019)
The present investigation provides a novel extension of the retrieving effectively from memory (REM) model to examine free-recall and recognition memory in older adults to inform our understanding of age-related cognitive decline. When some items on a list are strengthened through distributed repetitions, memory for the nonstrengthened items on that list may become impaired depending on how memory is tested—a phenomenon known as the list-strength effect (LSE; e.g., Tulving & Hastie, Journal of Experimental Psychology, 92, 297–304, 1972). When the strengthening operation involves distributed repetitions, LSE is robust in free recall, but it is reliably absent in recognition (Malmberg & Shiffrin, Journal of Experimental Psychology, 31, 322–336, 2005; Ratcliff, Clark, & Shiffrin, Journal of Experimental Psychology, 16, 163–178, 1990). Two experiments investigated LSE in recall and recognition in older adults and young adults who encoded items with full or divided attention. Despite showing impaired recall and recognition, older adults showed patterns of LSEs across both experiments that were similar to young adults with full attention rather than young adults with divided attention. In recognition, there was a null LSE in older and young adults, but a positive LSE was observed under divided attention. In contrast, in free recall, there was a positive LSE in older and young adults, but a null LSE under divided attention. Collectively, the results suggest that older adults do not have impaired encoding of context information (evidenced by intact LSE in recall), and they do not have impaired differentiation of item representations (evidenced by the null LSE in recognition). Age-related impairment in both memory tasks can be accounted for by sparse encoding of item-based information.